Efficient preparation of orders in a distributor coffee company using taboo search - Correa Espinal, Alexander; Rodríguez Velázquez, Elkin; Gómez Montoya, Rodrigo A; Hernández Vahos, José D. (TECCIENCIA, 2013)
The article aims to develop a taboo search metaheuristic to solve the routing travelling salesman problem (TSP) in the order picking process to obtain minimum distances when collecting products from the storage positions. The taboo search metaheuristic was implemented in the order picking of a coffee trading company in Antioquia, allowing the reduction of distance, time and cost of 44%, what amounts to a cost savings of 825000 a month and 825 minutes a month compared to a FLCL (Farthest Locations- Closest Location) routing strategy, currently being used by the company which allows to increase the efficiency of this operation.